المسؤولية الجنائية للفرد في الشريعة الإسلامية والقانون الدولي الجنائي دراسة مقارنة - Ahmad 'Abdullah Widan (Universiti Sains Islam Malaysia, 2024)
This study aims to analyze the criminal responsibility of individual in the case of committing international crimes and possibility of being put on trial at the International Crime Court as a subject of international law. In addition, this study addresses the issue from the Islamic view. In order to achieve his goal, the researcher uses the historical method mainly by highlighting significant events and historical developments related to the topic. The researcher also uses the descriptive analysis method to present the concept of criminal responsibility in positive and Islamic systems, with the aid of the comparative method for determining the similarities and differences. Furthermore, a critical approach has been used wherever necessary throughout this research. Finally, the researcher uses the inductive approach to extrapolate verses of the Holy Quran, prophetic tradition, sayings of the prophet’s companions, opinions of jurisprudential schools of thought, writings of thinkers of international criminal law, opinions of scholars on war and jihad presented in traditional jurisprudential sources, and facts related to our contemporary society. One of the most important results of this research is: The Islamic sharia has been a pioneer in the field of determination of parameters of international crime by special rules aim to deal with crimes in war and crimes against human dignity. The study showed that Islamic sharia has addressed these offenses without inclusion under the name of international crime. And the principle of immunity from criminal responsibility for the Head of State is not considered in Islamic law because he is a member of the Islamic community and subjects to the provisions of Islamic criminal law.